Estudos para uma métrica da aprendizagem do curso Domus Procel Edifica: integrando mapas conceituais e taxonomia revisada para um sistema inteligente de avaliação na web - Silva, Naira Vincenzi da (2013)
This study is a qualitative research project classified as practical and participatory action research designs, which has as its aim the creation of an instructional design, used as a learning metric for Domus Software - Procel Edification, which integrates concept maps and the revised Bloom taxonomy into an intelligent web assessment system. This metric aligns curriculum concept maps along with conceptual and procedural knowledge of the Domus software - Procel edifies the retaining cognitive processes, provides understanding and application, through offering a model of instructional design, which assigns weights to those cognitive processes attained by students and identifies principles to be used in its applicability for the evaluation of distance learning. The authors also present the results for alignment, inferring weights as well as an outline of the logical sequence along with steps for the implementation of the intelligent system through the association of some exemplification slides.